A polynomial f ( x ) with positive integer coefficients satisfies f ( 1 ) = 1 2 and f ( 1 2 ) = 2 0 8 0 . Find the last three digits of f ( 1 0 ) .
Details and assumptions
We are talking about all the numbers in their decimal representations.
You aren't given any information about the degree of the polynomial, except that it is positive.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Zi Song Yeoh , we really liked your comment, and have converted it into a solution. If you subscribe to this solution, you will receive notifications about future comments
First note that 1 2 3 < 2 0 8 0 < 1 2 4 and since f ( x ) has positive integral coefficients, we deduce that de g ( f ) < 4 .
If the degree is 1 , then f ( x ) = a x + b for a , b ∈ N but then a ≤ 1 1 and so 2 0 8 0 is not attainable.
If the degree is 2 then f ( x ) = a x 2 + b x + c for a , b , c ∈ N , but then a ≤ 1 0 and so 2 0 8 0 is still not attainable.
We're left with 3 and 2 0 8 0 can be attainable when de g ( f ) = 3 . We have f ( x ) = a x 3 + b x 2 + c x + d for a , b , c , d ∈ N . Thus we get two equations:
f ( 1 ) = a + b + c + d = 1 2 and f ( 1 2 ) = 1 7 2 8 a + 1 4 4 b + 1 2 c + d = 2 0 8 0
Subtracting the first from the second, we get:
1 7 2 7 a + 1 4 3 b + 1 1 c = 2 0 6 8 ⟹ 1 5 7 a + 1 3 b + c = 1 8 8
Since a , b , c , d are positive integers, clearly a = 1 . Since b ≤ 9 , we have ( b , c ) = ( 2 , 5 ) . Substituting back into the previous equation, we have d = 4 . And so:
f ( x ) = x 3 + 2 x 2 + 5 x + 4
Giving our desired answer:
f ( 1 0 ) = 1 2 5 4
Another method:
From the equation 1 7 2 8 a + 1 4 4 b + 1 2 c + d = 2 0 8 0 , we can take both sides of the equation mod 12 to get d ≡ 4 ( m o d 1 2 ) , which would imply d = 4 .
Using the same equation again, we have 1 7 2 8 a + 1 4 4 b + 1 2 c = 2 0 7 6 , and dividing by 1 2 yields 1 4 4 a + 1 2 b + c = 1 7 3 , from which we can find c = 5 .
Apply the same concept 2 more times to find a = 1 , b = 2 , and the answer follows.
Yeah, that's how you convert bases.
I did a pretty tedious (but foolproof) method that doesn't require finding out the degree:
Notice that f ( 1 2 ) − f ( 1 ) = 2 0 6 8 eliminates the constant term a 0 , and every term is of the form a k ( 1 2 k − 1 ) = 1 1 a k ( 1 2 k − 1 + 1 2 k − 2 + … + 1 2 + 1 )
Dividing 2068 by 11 gives 188. Since all the terms have ( 1 2 k − 1 + 1 2 k − 2 + … + 1 2 + 1 ) as a factor, 1 8 8 ≡ a n + a n − 1 + … + a 1 ≡ 8 ( m o d 1 2 )
Hence, a 0 = 1 2 − ( a n + a n − 1 + … + a 1 ) = 4 .
Using the same method twice (but being careful to subtract ( a k x k + a k − 1 x k − 1 + … + a 1 x + a 0 ) and divide by x k for each f ( x ) ), we get a 0 = 4 , a 1 = 5 , a 2 = 2 . The terms a k x k when x = 1 0 and k ≥ 3 are ≡ 0 ( m o d 1 0 0 0 ) and so we only need to know the aforementioned coefficients.
Thus, f ( 1 0 ) ≡ 1 0 0 a 2 + 1 0 a 1 + a 0 ≡ 2 5 4 ( m o d 1 0 0 0 )
Let f ( x ) = a n ⋅ x n + . . . + a 1 ⋅ x + a 0 . Since d e g ( f ) > 0 , we know 1 ≤ a i ≤ 1 1 For all i . Now f ( 1 2 ) = a 0 = 2 0 8 0 = 4 mod 1 2 , so a 0 = 4 . Similarly 1 2 f ( 1 2 ) − 4 = 1 2 2 0 7 6 = 1 7 3 = 5 mod 1 2 , so a 1 = 5 , and 1 2 2 f ( 1 2 ) − ( 5 ⋅ 1 2 + 4 ) = 1 4 4 2 0 1 6 = 1 4 = 2 mod 1 2 , so a 2 = 2 . Therefore, f ( 1 0 ) = 1 0 0 a 2 + 1 0 a 1 + a 0 mod 1 0 0 0 = 2 5 4 mod 1 0 0 0 .
Side note: Doing one more coefficient gives a 3 = 1 , and since a 3 + a 2 + a 1 + a 0 = 1 + 2 + 5 + 4 = 1 2 , we must have no more coefficients, so f ( x ) = x 3 + 2 x 2 + 5 x + 4 .
Let’s start by finding the degree of the polynomial . As, f ( 1 ) = 1 2 , the sum of the coefficients is 1 2 .Since each of them are positive , all the coefficients are less than 1 2 . We have f ( 1 2 ) = 2 0 8 0 and 1 2 3 = 1 7 2 8 .Then, without doubt the polynomial is a degree 3 polynomial (otherwise one of the coefficients have to be negative or greater than 1 2 ) .So, a ⋅ 1 2 3 + b ⋅ 1 2 2 + c ⋅ 1 2 + d = 2 0 8 0 .
This implies that a = 1 and by similar argument b = 2 . Thus we are left with 1 2 c + d = 6 4 and c + d = 9 . Solving these two equations, we get c = 5 and d = 4 . Finally, we are done with coefficients .So, f ( 1 0 ) = 1 0 0 0 + 2 0 0 + 5 0 + 4 = 1 2 5 4 ,hence the answer is 2 5 4 .
Problem Loading...
Note Loading...
Set Loading...
Let the polynomial be f ( x ) = a n x n + a n − 1 x n − 1 + . . . + a 1 x + a 0 . Note that f ( 1 ) is the sum of coefficients of the polynomial, so all coefficients are strictly smaller f ( 1 ) = 1 2 . Now, note that f ( 1 2 ) gives the coefficients of the polynomial in base 1 2 ! So, since f ( 1 2 ) = 2 0 8 0 , converting 2 0 8 0 to base 1 2 gives 1 2 5 4 , but note that since a 3 = 1 , a 2 = 2 , a 1 = 5 , a 0 = 4 are all less than 1 0 . Thus, f ( 1 0 ) gives a 3 a 2 a 1 a 0 = 1 2 5 4 and 1 2 5 4 ≡ 2 5 4 ( m o d 1 0 0 0 )